2017
DOI: 10.1111/ijfs.13415
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo studies on intragastric soya protein–polysaccharide gels in a beverage matrix

Abstract: Intragastric gelation is a mechanism whereby a consumed liquid food gels under the acidic gastric condition. It was hypothesised that intragastric gelation would result in satiety due to delayed gastric emptying. Three treatment beverages that is soya protein isolate (SPI) with k-carrageenan (SPI-LC; high viscosity, gelling), guar gum (SPI-GG; high viscosity) and no polysaccharide (SPI; low viscosity) were given to twenty participants in a randomised 3 9 3 double-blind within-subject crossover design trial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This is due to the increasing number of alginates available to associate with protein molecules to form an even stronger cross-linked gel network. Similar results were reported during in vitro gastric digestion of mixed whey protein and pectin as well as gelation of SPI and xanthan gum or carrageenan (Hu et al, 2017;Wee et al, 2017).…”
Section: Phsupporting
confidence: 87%
See 1 more Smart Citation
“…This is due to the increasing number of alginates available to associate with protein molecules to form an even stronger cross-linked gel network. Similar results were reported during in vitro gastric digestion of mixed whey protein and pectin as well as gelation of SPI and xanthan gum or carrageenan (Hu et al, 2017;Wee et al, 2017).…”
Section: Phsupporting
confidence: 87%
“…The effects of protein and polysaccharide interactions on functional properties have been reported (Jaramillo, Roberts, & Coupland, ; Lam, Paulsen, & Corredig, ; Lam, Shen, Paulsen, & Corredig, ; Yuan et al., ); however, whether and how polysaccharides influence soy protein digestion is not fully understood. Previous studies showed that solutions of mixed dairy proteins (whey and casein) or soy protein and negatively charged polysaccharides formed intragastric gels when the mixtures were added to simulated gastric fluid (SGF) (Borreani, Llorca, Larrea, & Hernando, ; Hu et al., ; Wee, Yusoff, Chiang, & Xu, ; Zhang, Zhang, & Vardhanabhuti, ). Intragastric gelation is believed to derive from the electrostatic interactions between positively charged patches on the proteins and negatively charged polysaccharides when pH changes from near neutral to acidic under simulated gastric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are many advantageous properties of polysaccharides, including nontoxicity, lack of side effects, improvement of immunity and antitumour, antidiabetic, hypolipidemic and antioxidant properties Yao et al, 2017). As polysaccharides are safe as functional food sources and have become more popular in recent years, it is important to conduct a value-oriented inquiry about D. aphyllum polysaccharides (Gao et al, 2017;Wee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A significant body of research has been directed to the nutritious and healthy properties of soybean and soy products. It has been found that soybean isoflavones and isoflavone-derived metabolites resemble estrogen and exhibit certain of its health benefits ( Chen et al, 2018 ; Wee et al, 2017 ; Bilal et al, 2014 ). Isoflavones include aglycones and their glycosides ( Hughes et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%